Dakwah Islam Dan Budaya Lokal (Resepsi Agama Dalam Kultur Nusantara) - Rasyid Alhafizh; Muhammad Fauzi; Zulfan Zulfan; Erman Erman (Prodi KPI FDPM IPMAFA Bekerjasama dengan Mafa Press IPMAFA Pati, 2024)
Da'wah is the core of Islamic teachings. In practice, da'wah can be carried out through various methods, approaches, and patterns that are tailored to the needs and situation of the community. slam does not result in the erosion of local traditions, wisdom, and culture. On the contrary, the process of acculturation between Islam and local culture actually enriches the variety of traditions and social practices of the region. The research method is qualitative by collecting data from library research and applying Comte's Social-Culture approach. The results obtained are the breadth of the Prophet Muhammad's teachings delivered through an effective socio-anthropological approach. A clear example is the Walisongo, who adapted the art of wayang performance to the building of places of worship, such as the Gedhe Kauman Mosque in Yogyakarta, Surau Tuo Sheikh Burhanuddin Ulakan, West Sumatra, Nurul Huda Mosque in Gelgel Village, Bali and many others. In addition, there are many forms of Islam-based local community receptions, such as the Grebeg tradition in the Yogyakarta Palace, Mauluik (maulid) of the Prophet Muhammad in West Sumatra, or the Bantai Adat Tradition in Merangin, Jambi, containing da'wah messages.